Comparison of Improving Effects for Diabetic Erectile Dysfunction according to the Anti-Glycemic Agents: Phlorizin and Insulin - Juhyun Park; Ohseong Kwon; Sung Yong Cho; Min Chul Cho; Jae-Seung Paick; Soo Woong Kim (The World Journal of Men's Health, 2019)
Purpose: To compare the improving effects of diabetic erectile dysfunction with two anti-glycemic agents; phlorizin and insu-lin. Materials and Methods: Sixty Sprague-Dawley rats were divided into four groups (n=15 in each group): normal control (C), untreated diabetic rats (D), and diabetic rats treated by phlorizin (P) or insulin (I). Ten weeks after the diabetic induction using an injection of streptozotocin (55 mg/kg), four weeks of diabetic control was conducted. Erectile response, Western blot, and immunohistochemistry were assessed. Results: During the experiment, the C-group showed continuous weight gain, while the other groups suffered from weight loss. After start of diabetic control, the body weight of I-group was increased; whereas, there was no meaningful change in the P-group. Meanwhile, comparable blood glucose levels were achieved in the P- and I-groups. The erectile response was markedly decreased in the D-group, whereas the P- and I-groups were similar as good as the C-group. In addition, D-group showed the significant decrease in the cavernosal smooth muscle content and increased apoptosis. Platelet endothelial cell adhesion molecule-1 protein expression, phosphorylation of endothelial nitric oxide synthase and myosin phosphatase target subunit 1 were significantly distorted in the D-group, while the P- and I-groups were comparable with the C-group. Conclusions: Phlorizin treatment resulted in the improvement of erectile function as same as insulin despite the lack of ana-bolic weight gains. These results suggest that control of blood glucose level rather than a type of anti-glycemic agents is more important for the prevention and treatment of diabetic erectile dysfunction